Mrgprb2-mediated mast cell activation exacerbates Modic changes by regulating immune niches - Ji, Zhongyin; Li, Jie; Tao, Siyue; Li, Hui; Kong, Xiangxi; Huang, Bao; Feng, Zhenhua; Wei, Xiaoan; Zheng, Zeyu; Chen, Jian; Chen, Binhui; Liu, Junhui; et al. (Experimental & molecular medicine, 2024)
Modic changes are radiographic features associated with microfracture, low-virulence organism infection and chronic inflammation with inflammatory cell infiltration in the vertebral endplate region. Mast cells, as innate immune cells similar to macrophages, are present in painful degenerated intervertebral discs. However, the involvement and mechanisms of mast cells in the development of Modic changes remain unclear. Herein, we found increased mast cell infiltration in samples from patients with Modic changes and in mouse models of Modic changes. To clarify the role of mast cells in the progression of Modic changes, we used mast cell-deficient (KIT W-SH/W-SH ) mice to construct a model of Modic changes and found that the severity of Modic changes in KIT W-SH/W-SH mice was significantly lower than that in WT mice. These findings were further supported by the use of a mast cell-specific activator (compound 48/80) and a stabilizer (cromolyn). Furthermore, we found that mast cells were not activated via the classic IgE pathway in the Modic change models and that Mrgprb2 is the specific receptor for mast cell activation reported in recent studies. Then, we utilized Mrgprb2 knockout mice to demonstrate that Mrgprb2 knockout inhibited mast cell activation and thus reduced the degree of Modic changes. Transcriptomic sequencing revealed aberrant PI3K-AKT and MAPK pathway activation in the Mrgprb2-deficient mast cells. Additionally, Mrgpbrb2-activated mast cells regulate immune niches by recruiting macrophages, promoting M1 polarization and reducing M2 polarization, thereby promoting the progression of Modic changes. These findings suggest that mast cells may serve as a novel therapeutic target for addressing Modic changes. Mast cells drive modic changes progression via Mrgprb2 activation Degenerative disorders of the lower back are common and can greatly affect life quality. The research by Ji et al. examines the role of mast cells (a kind of immune cell) in the development of these disorders. They discovered that mast cells aid in the progression of Modic changes (a type of spinal degeneration), by affecting the metabolism of the endplates (the ends of the spinal bones) and altering the immune response. This was shown through experiments with human tissue samples, animal models, and cell studies. The results suggest that focusing on mast cells could be a potential treatment for Modic changes. The research also emphasizes the significance of the Mrgprb2 receptor (a protein that activates mast cells) as a potential drug target. “This summary was initially drafted using artificial intelligence, then revised and fact-checked by the author.”